Navegación de robot movil en entornos domésticos basada en reconocimiento de objetos (2021)
This document presents a navigation system for a mobile robot in domestic environments based on object recognizing. First, it presents an evaluation of some state-art object detection networks using images of the simulator that was used in the project (Habitat-Sim). Then, it presents a full exploration of a domestic environment and the labeling of the points of a grid with the possible places of the environment. After that, it presents the clustering of the labels and the computing of the geometric center or a near navigable point to define the high-level graph. Finally, a navigation where a user choose a start and end point of the graph.